Partisipasi Pemuda pada Perjuangan PRRI dalam Novel Bergolak: Derita Anak Negeri karya Armini Arbain dan Ronidin - Vinta Nafila Khairil Putri; Syafril Syafril (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
This research examines social reflection in the novel Bergolak: Derita Anak Negeri by Armini Arbain and Ronidin, focusing on the forms and motives of youth participation in the PRRI events (1958-1961). The descriptive qualitative method and the Sociology of Literature approach are used to analyze the text of the novel. Data were analyzed by data reduction, classification of forms and motives of participation, and review of social reality with Ningrum's theory. The results showed that the youth and students, represented by Bahar, Sarman, and Karman, joined PRRI for various reasons. Their forms of participation included becoming spies, soldiers, and guerrillas. This participation comes without coercion, and the motives vary between characters. The social reality depicted in the novel is in line with the PRRI events written in historical documents. In conclusion, the novel Bergolak: Derita Anak Negeri presents a strong social reflection of the PRRI event through the forms and motives of youth participation.